"Government Bond: Its Effectiveness as a Financial Source In the Wake of Deterioration", A Case Study of Bank Mandiri Post-Merger - Prakarsa, Octavius Oky (2007)
The study conducts an evaluation case study of Bank Mandiri, an Indonesian state-owned bank, which merged from four previously leading state-owned banks that suffered in deterioration following the 1997 Asian Crisis.